Theft crimes in the hotspot regions in the Emirate of Ras Al Khaimah - Alketbi, Saeed; Alomosh, Ahmad (Al-Adab Journal, 2025)
This study aimed to identify theft crimes in the hotspot regions in the Emirate of Ras Al Khaimah. A statistical approach was used. The sample of the study consisted of (504) workers in the Ministry of Interior in the United Arab Emirates who work as police officers. The sample was purposive and non-probability one. The results of the study showed that the area where theft crimes affect the security of the Emirate of Ras Al Khaimah came with an arithmetic mean of (2.05) with a low degree. The reasons for spreading the theft crimes in the Emirate of Ras Al Khaimah came with an arithmetic average of (2.29) with a low degree. The field of factors that lead to theft crimes came with an arithmetic average of (2.23) with a low degree. The study recommends promoting the security presence, increasing the number of policemen and security patrols in the hotspot regions, and enhancing security control and surveillance to detect potential crimes and provide the necessary support to society.